Mislaid : a novel - Zink, Nell (Ecco, an imprint of HarperCollins Publishers, 2015)
"Stillwater College in Virginia, 1966. Freshman Peggy, an ingénue with literary pretensions, falls under the spell of Lee, a blue-blooded poet and professor, and they begin an ill-advised affair that results in an unplanned pregnancy and marriage. The two are mismatched from the start--she's a lesbian, he's gay--but it takes a decade of emotional erosion before Peggy runs off with their three-year-old daughter, leaving their nine-year-old son behind. Worried that Lee will have her committed for her erratic behavior, Peggy goes underground, adopting an African American persona for her and her daughter. They squat in a house in an African-American settlement, eventually moving to a housing project where no one questions their true racial identities. As Peggy and Lee's children grow up, they must contend with diverse emotional issues: Byrdie deals with his father's compulsive honesty; while Karen struggles with her mother's lies--she knows neither her real age, nor that she is "white," nor that she has any other family. Years later, a minority scholarship lands Karen at the University of Virginia, where Byrdie is in his senior year. Eventually the long lost siblings will meet, setting off a series of misunderstandings and culminating in a comedic finale worthy of Shakespeare" --